Different levels of the fermented yellow cornmeal in diets for jelawat, Leptobarbus hoevenii - HENDRY YANTO; JUNIANTO JUNIANTO; RITA ROSTIKA; YULI ANDRIANI; DEDI JUSADI (Nusantara Bioscience, 2017)
Yanto H, Junianto, Rostika R, Andriani Y, Jusadi D. 2017. Different levels of the fermented yellow cornmeal in diets for jelawat, Leptobarbus hoevenii. Nusantara Bioscience 9: 378-384. This research aimed to determine the optimum level of fermented yellow cornmeal in diets to improve the digestive enzyme activity, material digestibility coefficient, growth and feed efficiency for jelawat (Leptobarbus hoevenii Bleeker). The experimental treatments respectively used the fermented yellow cornmeal level of A1 (10%), A2 (20%), A3 (30%), A4 (40%), and two control groups of A5 (10% of unfermented yellow corn meal) and A6 (commercial diet). The experimental diets with the same protein (isonitrogenous) and energy (isocaloric) were given to jelawat with an average size of 32.51Â±0.21 g per fish. The results showed that Î±-amylase activity and carbohydrate digestibility value of the fermented yellow cornmeal increases along with the increasing feed levels. Protein and lipid of the body, retention of protein and lipid, daily growth rate and feeding efficiency were significantly different from each treatment (P<0.05). The fermented yellow cornmeal containing a level of 30% in the diet was the best for jelawat with an optimum level of 28.21-32.28% for the growth performance and feed efficiency of jelawat.